Presentation of antigenic peptides by products of the major histocompatibility complex. - Fairchild, P (1998)
Molecules encoded by the major histocompatibility complex (MHC) are polymorphic integral membrane proteins adapted to the presentation of peptide fragments of foreign antigens to antigen-specific T-cells. The diversity of infectious agents to which an immune response must be mounted poses a unique problem for receptor-ligand interactions; how can proteins whose polymorphism is necessarily limited bind an array of peptides almost infinite in its complexity? Both MHC class I and class II determinants have achieved this goal by harnessing a limited number of peptide side chains to anchor the epitope in place while exploiting conserved features of peptide structure, independent of their primary sequence. While class I molecules interact predominantly with the N- and C-termini of peptides, class II determinants form an extensive hydrogen bonding network along the length of the peptide backbone. Such a strategy ensures high-affinity binding, while selectively exposing the unique features of each ligand for recognition by the T-cell receptor.